Detection of hot-spot mutations in circulating cell-free DNA from patients with intraductal papillary mucinous neoplasms of the pancreas - Berger, Andreas W.; Hackert, Thilo; Strobel, Oliver; Büchler, Markus W. (Gastroenterology, 2016)
Intraductal papillary mucinous neoplasms (IPMNs) are the most frequent cystic pancreatic tumors. Little is known about their molecular alterations, but mutations in GNAS have been reported to promote IPMN formation. A tumor-derived fraction of circulating cell-free DNA (cfDNA), isolated from blood samples, contains many of the same mutations as the primary tumor, and could be a tool for noninvasive disease monitoring. We found that the total amount of cfDNA can discriminate between individuals without pancreatic lesions (controls) and patients with Fukuoka-negative branch-duct IPMN or pancreatic cancer. Furthermore, we detected GNAS mutations in cfDNA from patients with IPMN, but not in patients with serous cystadenoma or controls. Analyses of cfDNA might therefore be used in the diagnosis of patients with IPMN or in monitoring disease progression.